Uji Empat Jenis Bahan Trichokompos Terhadap Pertumbuhan dan Hasil Tanaman Sawi (Brasicca juncea L.) - Abdi Gunawan; Jumar Jumar; Ronny Mulyawan (Agroekotek View, 2022)
Mustard plant is a plant that has profitable business prospects because it has short life and high market demand. Meanwhile, mustard production has decreased this is due to the excessive use of chemical fertilixers which can damage the soil. Wrong one effort that can be done to overcome this is to switch to using organic fertilizers, one of the organic fertilizers is trichocompost. Trichompost fertilizer is an organic material which the breakdown is assisted by beneficial microorganisms. Material that can be used for make it cattle manure. This study aims to determine the effect of trichocompost chicken manure, goat manure on growth and yield of mustard (Brassica Juncea L.), and knowing the best treatment trichocompost manure on the growth and yield of mustard (Brassica Juncea L.). this research was conducted from March to May 2021, and took place at the Greenhouse Program Study of Agroecotechnology, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru. This research using Completely Randomized Design (CRD) method with a single factor, namely the type of fertilizer trichocompost with different materials, this study used 6 treatments for each treatment repeated 4 times so that 24 experimental units were obtained, namely: P0 (Control), P1 (Trichokompos chicken manure 10 tons.ha-1), P2 (Trichcompost cow dung 10 tons.ha-1), P3 (Trichcompost goat manure 10 tons.ha-1), P4 (Trichocompost quail droppings 10 tons.ha-1), and P5 (Trichcompost combination that is, each trichocompost is given 2.5 tons.ha-1). Observation parameters in this study The number of leaves, leaf width, stem diameter, and plant wet weight. The results of the study show that the application of trichocompost fertilizer did not have a significant effect on the number of leaves, leaf width, stem diameter, and wet weight on mustard plants. Treatment that shows more valuehigh namely in the P5 treatment (combined trichocompost), where in the observation indicator of the average number of leaves is nine pieces, an average leaf width of 6.05 cm, an average stem diameter of 0.66 cm, and an average weight of wet average 9.85 g.